PENGARUH JENIS PUPUK ORGANIK DAN UREA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELEDRI (Apium graveolus L.) - Netty Syam; Suriyanti Suriyanti; Lilla Hasni Killian (Percetakan Umi Toaha Makassar, 2017)
The objectives of the research were to find out type of organic fertilizer and urea doses to improve the yield of celery. The experiment was arranged using Randomized Block Design with factorial design.The first factor were cow manure, compost and chicken manure and the second factor were urea dosage 240 kg/ha, 270 kg/ha and 300 kg/ha.The results showed that organic fertilizer treatment in the form of chicken manure and urea 300 kg/ha resulted in plant height, leaf number, number of tillers, root volume and wet weight in celery were highst. The highest number of tillers was 6.27 plants and wet weight 14.69 g per plant.